Barriers to accurate diagnosis and effective management of heart failure have not changed in the past 10 years: a qualitative study and national survey. Issue 3 (1st April 2014) - Hancock, Helen C; Close, Helen; Fuat, Ahmet; Murphy, Jerry J; Hungin, A Pali S; Mason, James M
Abstract : Objectives: To explore changes in healthcare professionals' views about the diagnosis and management of heart failure since a study in 2003. Design: Focus groups and a national online cross-sectional survey. Setting and participants: Focus groups (n=8 with a total of 56 participants) were conducted in the North East of England using a phenomenological framework and purposive sampling, informing a UK online survey (n=514). Results: 4 categories were identified as contributing to variations in the diagnosis and management of heart failure. Three previously known categories included: uncertainty about clinical practice, the value of clinical guidelines and tensions between individual and organisational practice. A new category concerned uncertainty about end-of-life care. Survey responses found that confidence varied among professional groups in diagnosing left ventricular systolic dysfunction (LVSD): 95% of cardiologists, 93% of general physicians, 66% of general practitioners (GPs) and 32% of heart failure nurses. For heart failure with preserved ejection fraction (HFpEF), confidence levels were much lower: 58% of cardiologists, 43% of general physicians, 7% of GPs and 6% of heart failure nurses. Only 5–35% of respondents used natriuretic peptides for LVSD or HFpEF. Confidence in interpreting test findings was fundamental to the use of all diagnostic tests. Clinical guidelines were reported to be helpful when diagnosing LVSD by 33% of nurses and 50–56% of other groups, but fell to 5–28% for HFpEF. Some GPs did not routinely initiate diuretics (23%), ACE-inhibitors (22%) or β-blockers (38%) for LVSD for reasons including historical teaching, perceived side effects and burden of monitoring. For end-of-life care, there was no consensus about responsibility for heart failure management. Conclusions: Reported differences in the way heart failure is diagnosed and managed have changed little in the past decade. Variable access to diagnostic tests, modes of care delivery and non-uniform management approaches persist. The current National Health Service (NHS) context may not be conducive to addressing these issues.